2017
DOI: 10.1111/tbj.12780
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Pregnancy: Avoiding Fetal Harm When Maternal Treatment Is Necessary

Abstract: The management of breast cancer during pregnancy poses unique challenges and requires a multidisciplinary approach. In this review, we discuss the treatment of breast cancer in pregnancy and recent updates regarding the safety of surgical and chemotherapeutic treatments, including both oncologic and fetal outcomes. The treatment of breast cancer during pregnancy mirrors that outside of pregnancy, with a few important differences dictated by the balance of maternal versus fetal health. Overall, surgical treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 31 publications
(61 reference statements)
0
44
0
8
Order By: Relevance
“…Although there is a dearth of information on the relationship between PABC and non‐Caucasian race, one study has suggested a higher proportion of PABC cases among minority races . Although there is some debate in the literature, PABC is often associated with hormone receptor negative and HER2 enriched cancers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a dearth of information on the relationship between PABC and non‐Caucasian race, one study has suggested a higher proportion of PABC cases among minority races . Although there is some debate in the literature, PABC is often associated with hormone receptor negative and HER2 enriched cancers …”
Section: Discussionmentioning
confidence: 99%
“…The postpartum period is variably defined in the literature, ranging from 1 to 5 years after a pregnancy . PABC is currently estimated to affect 1 in every 3000 breast cancer patients, with this incidence expected to rise as breast cancer among young women becomes more common, and greater numbers of women are choosing to delay childbearing …”
Section: Introductionmentioning
confidence: 99%
“…8 Surgical treatment is considered safe to be performed at any trimester of pregnancy, with mastectomy being the surgery of choice. 8,9 Whether to perform or not a sentinel lymph node biopsy during the procedure remains without consensus in the literature. 8 Chemotherapy can also be performed after the first trimester of pregnancy, taking care to avoid certain chemotherapeutic drugs such as methotrexate.…”
Section: Discussionmentioning
confidence: 99%
“…8 Chemotherapy can also be performed after the first trimester of pregnancy, taking care to avoid certain chemotherapeutic drugs such as methotrexate. 9 Radiotherapy, hormone therapy and use of monoclonal antibodies are contraindicated during pregnancy. 8,9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation